Relationship of Peer Social Support and Past Experience of The Risk of Bullying Behavior in Adolescents - Meylina Widyastuti; Lita Heni Kusumawardani; Wahyudi Mulyaningrat (Centre of Applied Science for Pharmaceutical Science Universitas Jenderal Soedirman, 2024)
Background: Bullying can occur among school students and is dominated by adolescents. This has an impact not only on the people involved but those who see the incident will also feel it. Social factors of friends and bad experiences in childhood are also factors that influence the risk of bullying behavior. This study aimed to determine the relationship between peer social support and past experience on bullying risk behavior in adolescents. Methods: This research used a cross-sectional design method with consecutive sampling with analyses of Spearman’s test. The research was conducted on adolescents aged 12-15 years at Junior High School 2 Kedungbanteng. The instrument used is PSS-Fr, Olweus Bully/ Victim Questionnaire, and Atfiyanah. Results: This research showed that the number of respondents was dominated by men coming from grade 7. The peer social support and risk of bullying behavior variables have median scores of 13 and 12. The prevalence of victims of bullying in Junior High School 2 Kedungbanteng students is 41.3%. There was no significant relationship between peer social support and past experience of the risk of bullying behavior. Conclusion: There was no significant relationship between peer social support and past experience of the risk of bullying behavior. Keywords: Adolescent; past experience; peer social support; risk bullying behavior